STRATEGI PENDEKATAN MANAJEMEN KELAS DALAM OPTIMALISASI PROSES PEMBELAJARAN DI SEKOLAH DASAR - Arief Suci Kurniasihanto (STKIP Pesisir Selatan, 2026)
Classroom management is an important aspect of the learning process in elementary schools as it plays a significant role in creating a conducive, orderly, and effective learning environment. This study aims to analyze classroom management approaches in optimizing the learning process in elementary schools. The research employed a qualitative approach using a library research method, drawing data from various books, journal articles, and previous studies relevant to classroom management. The findings indicate that the implementation of preventive, behavioral, socio-emotional, and collaborative approaches can assist teachers in creating a comfortable learning environment, improving student discipline, encouraging active participation, and enhancing learning motivation. Furthermore, effective classroom management can minimize disruptions during the learning process, thereby enabling learning objectives to be achieved optimally. Therefore, teachers need to integrate various classroom management approaches according to students’ characteristics and learning conditions in order to create a more effective and meaningful learning process.